2022
DOI: 10.1007/s10162-022-00864-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Electrically Evoked Compound Action Potential over time After Implantation and Subsequent Deafening in Guinea Pigs

Abstract: The electrically evoked compound action potential (eCAP) is a direct measure of the responsiveness of the auditory nerve to electrical stimulation from a cochlear implant (CI). CIs offer a unique opportunity to study the auditory nerve’s electrophysiological behavior in individual human subjects over time. In order to understand exactly how the eCAP relates to the condition of the auditory nerve, it is crucial to compare changes in the eCAP over time in a controlled model of deafness-induced auditory nerve deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Of particular interest was the peculiar localization of pAKT on the surface of pillar cells’ apical region. According to pillar cell structure, the apical region contains dense actin meshes [ 27 ], which could probably promote the localization of pAKT in the observed region. Moreover, we did not observe any differences in the PTEN protein levels between the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest was the peculiar localization of pAKT on the surface of pillar cells’ apical region. According to pillar cell structure, the apical region contains dense actin meshes [ 27 ], which could probably promote the localization of pAKT in the observed region. Moreover, we did not observe any differences in the PTEN protein levels between the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental procedures were approved by the Dutch Central Authority for Scientific Procedures on Animals (CCD: 1150020174315). Only female guinea pigs were included in the study based on their easier handling compared to males (as reported previously [ 27 ]) and to exclude any sex-related mTOR differences [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, a cochleostomy was manually performed with a 0.5 mm hand drill, just below (∼0.5 mm) the round window (POST1). This method has been previously performed without causing noticeable threshold shifts and/or hair cell loss ( Ramekers et al, 2015 , 2022 ). After the cochleostomy, a custom-made electrode array (Advanced Bionics; diameter 0.5 mm, length basal electrode to tip 3.5 mm, inter-electrode distance 1.0 mm) was inserted ∼4 mm into scala tympani (POST2) with all 4 electrodes of the array positioned intracochlearly.…”
Section: Methodsmentioning
confidence: 99%
“…The eCAP has been shown to be useful for estimating the physiological status of the auditory nerve [3][4][5][6][7][8][9]. These estimates of the physiological status of the auditory nerve may have clinical benefits such as longitudinal monitoring of neural health [10,11], implant fitting [12][13][14] and explaining variance in speech perception performance among CI users [9,[15][16][17][18]. The primary challenge in recording eCAPs is the presence of unwanted voltages (i.e., electrical artifacts) that contaminate and obscure the neural response.…”
Section: Introductionmentioning
confidence: 99%
“…The eCAP has been shown to be useful for estimating the physiological status of the auditory nerve [39]. These estimates of the physiological status of the auditory nerve may have clinical benefits such as longitudinal monitoring of neural health [10, 11], implant fitting [1214] and explaining variance in speech perception performance among CI users [9, 1518].…”
Section: Introductionmentioning
confidence: 99%